Impacts of wheat seed storage at poor household level in Bangladesh (Bangladesh Journal of Agricultural Research, 2018)
Small and marginal farmers have little access to improved seed from institutional sources and are thus largely excluded from the benefits of new varieties. The production and storage of improved varieties seeds at the household (HH) level can successfully overcome this problem. With this aim CSISA-CIMMYT (Cereal Systems Initiative for South Asia) project in Bangladesh have been working since 2012. Therefore, the study assessed the impacts of wheat seed storage systems at HH level, with a particular emphasis on how the poor farmers are benefited by doing the seed storage business. The study analyzed data and information collected at random from 210 supported and 60 non-supported farmers spread over three wheat growing districts namely Mymensingh, Faridpur and Rangpur. Wheat farmers used different storage containers and showed the highest level of satisfaction towards plastic sac along with poly bags and plastic/metal drum due to cost effectiveness and seed quality maintenance. On an average, supported and non-supported farmers retained respectively 103 kg and 100 kg of seed at household level, and sold most of their seeds to neighbouring farmers, local markets, and dealers. Wheat seed storage at household level was a profitable business to most of the respondent farmers. They could earn a reasonable net income (Tk.1127-Tk.1210) from seed storage. The farmers who stored seed in plastic/metal drum received the highest net income due to higher storage capacity, less storage cost, and higher seed price. The wheat storage program has created significant impacts in the study areas. A substantial increase was recorded in wheat area, wheat productivity, and financial benefit of the wheat farmers as a whole. Nevertheless, improved wheat seed is now available at farm level and most farmers become enthusiastic towards improved wheat cultivation because of this program. Respondent farmers did not face any critical problem during seed storage.Bangladesh J. Agril. Res. 43(2): 345-360, June 2018